2012
DOI: 10.1108/00242531211259328
|View full text |Cite
|
Sign up to set email alerts
|

Plugging the “whole”: librarians as interdisciplinary facilitators

Abstract: PurposeThe purpose of this paper is to examine some of the obstacles to interdisciplinary research and examine some ways that academic librarians can help to overcome them.Design/methodology/approachA broad review of the literature of the social sciences was reviewed for descriptions of difficulties that interdisciplinary researchers encounter. General developments in librarianship from library literature were then applied as a starting point for discussing ways that librarians can provide important services t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…While there has been some speculation as to whether these initiatives would be sustainable after the QEP funding had been spent (Jumonville, 2014), the literature suggests that librarian collaboration with faculty and support centers on campus has remained and grown as a vital part of library outreach by: creating course-specific LibGuides with faculty input (Little, Fallon, Dauenhauer, Balzano, & Halquist 2010); supporting interdisciplinary research across departments (Knapp, 2012;Gauder & Jenkins, 2012); partnering with campus writing centers (Ferer, 2012); co-teaching and assignment design (Ferer, 2012); incorporating learning theories and ACRL concepts to create measureable outcomes (Porter, 2014;Jumonville, 2014); and embedding librarians in semester-long courses (Knapp, 2012;Reale, 2016). As a result of these QEP initiatives, librarians play a more holistic, or "blended librarian" role in course collaboration, instruction design, and development, which goes beyond the traditional one-shot introduction to library resources session, although this is still an integral component of library outreach (Knapp, 2012). However, the role of instructor-librarians is still a work in progress.…”
Section: Literature Reviewmentioning
confidence: 98%
“…While there has been some speculation as to whether these initiatives would be sustainable after the QEP funding had been spent (Jumonville, 2014), the literature suggests that librarian collaboration with faculty and support centers on campus has remained and grown as a vital part of library outreach by: creating course-specific LibGuides with faculty input (Little, Fallon, Dauenhauer, Balzano, & Halquist 2010); supporting interdisciplinary research across departments (Knapp, 2012;Gauder & Jenkins, 2012); partnering with campus writing centers (Ferer, 2012); co-teaching and assignment design (Ferer, 2012); incorporating learning theories and ACRL concepts to create measureable outcomes (Porter, 2014;Jumonville, 2014); and embedding librarians in semester-long courses (Knapp, 2012;Reale, 2016). As a result of these QEP initiatives, librarians play a more holistic, or "blended librarian" role in course collaboration, instruction design, and development, which goes beyond the traditional one-shot introduction to library resources session, although this is still an integral component of library outreach (Knapp, 2012). However, the role of instructor-librarians is still a work in progress.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The concerns behind the development of Semantic Web technologies are similar to those expressed by the library community and the fact that standards like MARC are now considered outdated pushes information professionals to consider these technologies as a viable option (Alemu, Stevens, Ross & Chandler, 2012;Coyle, 2010). Considering that information science, just like the Semantic Web, is interdisciplinary and multidisciplinary in nature and directly connected to information technology and computer science (Holland, 2008;Knapp, 2012;Paul-Hus, Mongeon & Shu, 2016;Saracevic, 1995;Szostak, 2008), and that Semantic Web technologies can be relevant in almost all disciplines, it is interesting to study the contribution of information science in that research landscape and the feedback of the discipline to the broader Semantic Web community.…”
Section: Introductionmentioning
confidence: 99%
“…Inferred from his analysis was the role that reference librarians must play in facilitating access to information necessary in the pursuit of interdisciplinary investigations. Other authors identified similar issues associated with the information-seeking behavior of interdisciplinary scholars and the implications these have for reference services (Jamali & Nicholas, 2010;Knapp, 2012;McNamara & Matre, 2002;Palmer, 2010;Woodside, 2009). However, much of this literature focuses on traditional resource-based learning methods rather than analyzing ways that the library can support specific interdisciplinary learning objectives articulated in the broader educational research literature (Repko, 2012).…”
Section: Performing Interdisciplinarity In Librarianshipmentioning
confidence: 99%
“…As long-standing and deeply rooted parts of the academy, libraries have been caught up in these recurring ebbs and flows. Much of the current literature suggests that librarians struggle to effectively anticipate the impact of interdisciplinary practice on the provision of public services (Bates, 1996;Knapp, 2012;Palmer, 1996). As a consequence, most practice-based research examining the impact of interdisciplinarity on library services is descriptive or etiologic, with overlapping themes of interdisciplinarity viewed in at least three ways: as a collaborative process in research and teaching between librarians and faculty; as a way to describe the nature of courses being taught; or as a problem for collection-building and reference services.…”
Section: Performing Interdisciplinarity In Librarianshipmentioning
confidence: 99%